Securing air defense visual information with hyperchaotic Folded Towel Map-Based encryption - Shamsa Kanwal; Saba Inam; Fahima Hajjej; Ala Saleh Alluhaidan (AIMS Mathematics)
In modern air defense systems, safeguarding sensitive information is crucial to prevent unauthorized access and cyber-attacks. Here, we present an innovative image encryption approach, leveraging chaotic logistic maps and hyperchaotic Folded Towel Map sequence generation. The proposed image encryption is a multi-layered procedure intended to secure image transmission. It initiates with permutation, where a chaotic logistic map generates pseudo-random sequences to scramble pixel positions. Next, key mixing creates complexity, randomness, and nonlinearity using an invertible key matrix. Finally, the diffusion phase employs hyperchaotic maps to produce a new sequence XORed with the pixels through a bitwise operation, further encrypting the image. This three-stage process efficiently protects images from unauthorized access, ensuring secure transmission. The proposed method enhances security by leveraging non-linearity, sensitivity, and robust mixing, properties making it highly resistant to cryptographic attacks. The experimental results showed robust encryption performance as established by metrics such as an entropy value of 7.9991, a UACI of 33.21%, and an NPCR of 99.61%. The proposed encryption approach outperformed existing methods in securing image transmission and storage, offering a reliable solution for protecting air defense communication strategic data.